A brief history of the Department of Cosmoecology and Cosmic Mineralogy (to 50-anniversary of M. P. Semenenko Institute of Geochemistry, Mineralogy and Ore Formation NAS of Ukraine) - Semenenko, V. P. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2019)
The history of origin and evolution in Ukraine of mineralogical studies of cosmic samples, mainly meteorites, and the main stages of formation of the Department of Сosmoecology and Cosmic Mineralogy at the M. P. Semenenko Institute of Geochemistry, Mineralogy and Ore Formation and the Institute of Environment Geochemistry of the National Academy of Sciences of Ukraine are given. It is shown, that the basis of mineralogical study of meteorites, their gathering and collectibility in Ukraine was founded by academician V.I. Vernadsky in the 1930’s. Since 1969 the mineralogical studies of meteorites were provided at Lviv University, and cosmochemical ones did at the Institute of Geochemistry and Physics of Minerals of the Academy of Sciences of Ukraine. Academicians M. P. Semenenko, E. K. Lazarenko, E. V. Sobotovich, docent A. A. Yasinskaya were organizers and ideologists of these studies. In 1987 E. V. Sobotovich realized the idea of E. K. Lazarenko and created within the Department Nuclear Geochemistry and Cosmochemistry a laboratory of Cosmic Mineralogy, which was eventually transformed into the Department of Cosmoecology and Cosmic Mineralogy. Data on the main stages of the department development, its main scientific directions and the most important results of the cosmic material study are given. Importance of the department support by the well-known Western scientific centers, as well as joint with them research projects, realized on the modern instrumental basis, is remarked. Special attention to expeditionary work of the department on the meteorites gathering, the perspectives of their study, and current problems, which is connected with limited possibilities of cosmic samples collecting, the modern level of research as well as impact of political and social disasters on the evolution of fundamental science is accentuated.